Avaliação microbiológica e parasitológica nos processos de higienização de alfaces (Lactuca sativa L.) de diferentes cultivos - Costa, Eveline de Alencar (2011)
The vegetables sanity that are eaten raw is a relevant factor to health must be ensured by sanitizing with chemicals that have effective action to eliminate, reduce and / or removal of contaminants. The traditional way of cleaning includes washing vegetables under running water followed by immersion in 200ppm chlorine solution and rinse to remove dirt and remnants of the chemical waste. However, some studies indicate that this sanitization does not guarantee the safety of vegetables, for though while reduces the microbial load, it is not efficient in the elimination of some parasitic forms. Therefore, this study aimed to detect microorganisms, protozoa, helminths and arthropods in lettuce (Lactuca sativa L.), curly variety, from conventional farming, organic and hydroponic, in its fresh form and after two methods of cleaning: test (application of detergent and chlorine solution to 200ppm) and traditional (use of only a 200ppm chlorine solution). All lettuce were contaminated by fecal coliforms, but the hydroponic and organic samples had mean values within the standard stipulated by law, 21±74NMP/g and 24±40 NMP/g, respectively) unlike the conventional (152 ± 286NMP/g). In 100% of the samples of conventional and organic lettuces were not contaminated with Salmonella sp. but 20% of hydroponic samples were contaminated by this pathogen, being classified as unfit for consumption. In parasitological analyses were detected in organisms potentially pathogenic to humans: Giardia sp cysts. (2), eggs of Ascaris sp. (6) and eggs of Taenia sp. (1), with six occurrence in three lettuces in conventional and organic. Giardia sp cysts. (2), eggs of Ascaris sp. (6) and eggs of Taenia sp. (1), with six occurrence in three lettuces in conventional and organic. Yet been detected amoeba cysts and larvae of nematodes morphologically similar to those found in man, but more likely were forms of life free from the earth. Forms were observed in abundance among free-living protozoa, nematodes, helminths, and arthropods (especially those in hydroponic lettuce) served in lettuce dirt, reflecting the composition of culture environments. Evaluating the two processes of sanitization studied it was found that the mean of fecal coliform in the different types of lettuce was lower in the test method than the traditional, with increased efficiency. The stage of pre-washing reduced by 60% the initial contamination of fecal coliform, the detergent wash was effective when compared with the reduction achieved in the next step. The traditional method promoted significant decrease in the initial contamination of fecal coliform bacteria, however, no significant difference when compared with the test method or with the step of washing with detergent alone, proving once again its effectiveness. For removal of the forms of helminths, protozoa and arthropods in general, both methods were effective, showing no significant difference. When analyzed separately the different stages of cleaning procedures, it was found that there were significant for the removal of helminths, with better efficiency of the testing procedure, which may suggest that the cleaning with detergent performed only achieve the same results of detergent and chlorine. Thus, we conclude that test hygienization, both for the removal of helminths as to reduce fecal coliform bacteria, showed greater efficacy.